Transmit power optimization for video transmission over slowly-varying Rayleigh-fading channels in CDMA systems. - Il-Min Kim
An optimum transmit power management scheme is proposed for wireless video service in code-division multiple-access systems. The scheme minimizes the transmit power subject to the constraint on the distortion resulted from the loss of each packet and the error propagation effect caused by the motion compensation. It implicitly controls the target bit-error rate (BER) of the video packet according to the importance of the packet. The more important the packet is, the more securely it is transmitted over noisy channel. Furthermore, the scheme adjusts the target BER as if the water filling concept is applied to the problem of minimizing the transmit power. The simulation results show that the proposed scheme considerably outperforms the conventional schemes.
Keywords: BER; CDMA system; Bit error rate; Code division multiple access; Error propagation effect; Motion compensation; Noisy channel; Optimum transmit power management scheme; Secure transmission; Slowly-varying Rayleigh-fading channels; Transmit power optimization; Video packet; Video transmission; Water filling concept; Wireless video service